Assessing the Value of a Novel Augmented Reality Application for Presurgical Planning in Adolescent Elbow Fractures - Laguna, Benjamin; Livingston, Kristin; Brar, Ravinder; Jagodzinski, Jason; Pandya, Nirav; Sabatini, Coleen; Courtier, Jesse (Frontiers in Virtual Reality, 2020)
Objectives: We retrospectively assess the potential impact of a novel, investigational Augmented Reality (AR) software application, RadHA (Radiology with Holographic Augmentation), on pediatric orthopedic surgeon’s confidence in surgical planning, hardware selection, hardware fit, and estimated potential intra-operative time savings in the setting of complex adolescent elbow fractures. Methods: After study selection, 12 individual cases of complex elbow fractures in adolescent pediatric patients were identified for review. AR models were generated for each case derived from the patient’s CT. Five fellowship-trained pediatric orthopedic surgeons reviewed each case for a total of 60 separate observations. Surgeons reviewed clinical data, radiologic imaging, and AR models, and then answered Likert Scale questions on measures of confidence in presurgical planning and projected potential time savings. These data were reviewed and analyzed using various statistical tools. Results: Surgeons reported high confidence in the quality of the AR models created. Additionally, surgeons reported increased confidence in their surgical plan, increased confidence in hardware selection, and increased confidence in hardware fit. Within the sub-analysis of complex (comminuted) fractures, surgeons reported greater expected increases in confidence of their surgical plan and hardware fit. Overall, surgeons estimated potential intra-operative time savings, averaging 17.3 minutes for all fracture types, and 17.6 minutes for complex fractures. Conclusions: Preoperative planning using AR-based models can increase surgeon confidence in preoperative planning, hardware selection, and confidence in hardware fit.